A numerical investigation of combined solar chimney and water wall for building ventilation and thermal comfort. (15th March 2020) - Wang, Haoyu; Lei, Chengwang
Abstracts: This paper reports a numerical investigation of combined solar chimney and water wall for building ventilation and thermal comfort. The effects of major design parameters including glass panel thickness, air gap width and water column thickness are investigated with CFD simulations. The results show that the combined system is capable of providing around-the-clock ventilation with a daily average of 4.1 air changes per hour while maintaining the daily average of the room temperature 4.8   °C above that of the ambient. The overall performance of the combined system may be further improved by reducing the glass panel thickness or applying solar control tinting to the water wall assembly, and as much as 7.3% and 5.2% improvements in the ventilation rate and the averaged room temperature respectively can be achieved. Increasing the water column thickness by 0.1 m leads to 4.9% or more improvement in the ventilation rate but will cause the averaged room temperature to drop by 6.4% when the water column thickness is increased to 0.3 m. Increasing the air gap width from 0.1 m to 0.2 m leads to 13.9% improvement in the ventilation rate without affecting the averaged room temperature much. However, further increasing the air gap width only has a minor impact on the ventilation rate. Highlights: Combined solar chimney and water wall system attached to a room is studied by CFD. The combined system generates daily averaged ventilation of 4.1 ACH. The room temperature is kept 4.8 °C over the cool ambient with ventilation. Smaller glass panel thickness and tinted water wall further improves performance. Bigger air gap width and water column thickness improves ventilation rate.